An Analysis of the Co-Movement Effects between the International Gold Market and Stock Market (Journal of humanities and social sciences exploratio, 2025)
This paper analyzes the co-movement effects between the international gold market and the stock market, examining their dynamic linkages and drivers across different phases of the economic cycle. The study finds that the linkage between gold and stocks exhibits pronounced time variation and asymmetry, influenced by multiple factors including the macroeconomic environment, monetary policy, and geopolitics. During expansions, equity markets typically rise on improved earnings expectations, while the gold market—affected by higher real interest rates and stronger risk appetite—may display a positive correlation or a weak negative correlation with equities. For example, in Q1 2025, expectations of Federal Reserve rate cuts lifted gold-related equities; although bullion prices corrected, expectations regarding inflation and economic recovery continued to support the value of gold assets. By contrast, amid extreme events such as financial crises or geopolitical conflicts, gold’s safe-haven property becomes salient, producing a clear negative correlation with equities. For instance, early in the COVID-19 pandemic in 2020, global stocks plunged while gold prices rose against the trend, followed by a brief joint decline caused by a liquidity-driven sell-off. Key drivers of the co-movement include: (1) monetary policy: in easing cycles, low interest rates reduce the opportunity cost of holding gold while ample liquidity supports equities, allowing both to strengthen simultaneously; (2) hedging strategies: futures hedges by gold producers can cause gold-mining shares to lag bullion prices—for example, in 2024 Shandong Gold’s hedging losses weighed on its share price; (3) cost structures: low-cost miners show greater resilience during bullion volatility—for example, in 2025 Zijin Mining outperformed gold futures due to cost advantages. The findings suggest that investors should dynamically adjust asset allocation to combine gold’s safe-haven attributes with the growth potential of equities, while monitoring corporate hedging practices, macro policy, and geopolitical risk. Regulators should enhance cross-market risk surveillance and advance gold-market reforms to improve linkage efficiency. Future research may further investigate cross-industry differences in stock–gold co-movement and the potential of artificial intelligence in cross-market strategies.
Keywords: gold market; stock market; co-movement effects; dynamic correlation; safe-haven property; monetary policy